Detecting mental health problems after paediatric acquired brain injury: A pilot Rasch analysis of the strengths and difficulties questionnaire. Issue 7 (9th August 2021) - McCarron, Robyn Henrietta; Gracey, Fergus; Bateman, Andrew
ABSTRACT: The parent-reported Strengths and Difficulties Questionnaire (SDQ-P) is commonly used to assess for mental health problems, but its psychometric properties have not been studied in the paediatric Acquired Brain Injury (ABI) population. This study investigated the properties of the SDQ-P and its subscales in this population using Rasch analysis. One hundred and forty-three SDQ-Ps and 123 Impact Supplements were analyzed. Sixty-nine percent of SDQ-Ps were completed by female carers, 59% of young people were male, and 58% had Traumatic Brain Injury (TBI). In this population the SDQ-P Total Difficulties Scale and the Conduct Problems subscale showed questionable construct validity. The individual subscales and Impact Supplement did not meet the criteria for reliability. Two items had disordered thresholds. The individual subscales showed mistargeting and 13–24% person misfit. Two items were significantly underdiscriminating. There was differential item functioning with age and time post-injury, and local dependence between subscale items. The Total Difficulties scale was multidimensional. The most easily endorsed items were in keeping with common symptoms of brain injury. These findings suggest the SDQ-P in its current form may not be a reliable and valid assessment measure for mental health difficulties in the paediatric ABI population and requires further investigation.